Perception locale de la dynamique du peuplement ligneux des vingt dernières années au Sahel burkinabé - Pounyala Awa Ouoba; Evariste Constant Da Dapola; Souleymane Pare (VertigO)
West African Sahel suffered negative narrations about its environmental dynamic since the 1970s drought. Many conducted researches were mainly based on drivers and impacts of ecosystems degradation. Despite some ethno-botanic studies on environment dynamic in the Sahel area of Burkina Faso, there is a gap of knowledge on farmers’ perceptions. Using a survey of 194 household, this study analyzes the perceptions of woody vegetation dynamic by farmers in three villages sites located in the sahelian zone of Burkina Faso. In general, results show that the majority of household perceive land cover degradation. Some of the respondents reported an increasing of vegetation cover with a statistically significant difference among the three study sites. Based on these results it is important to take into account individual perceptions to support the sustainability of the natural resources conservation and management.